Application of the center manifold theory to the study of slewing flexible Non-ideal structures with nonlinear curvature: a case study - Fenili, A.; Balthazar, J. M. [UNESP]; Mook, D. T.; Weber, H. I. (The Brazilian Society of Mechanical Sciences, 2002)
In this paper is Analyzed the local dynamical behavior of a slewing flexible structure considering nonlinear curvature. The dynamics of the original (nonlinear) governing equations of motion are reduced to the center manifold in the neighborhood of an equilibrium solution with the purpose of locally study the stability of the system. In this critical point, a Hopf bifurcation occurs. In this region, one can find values for the control parameter (structural damping coefficient) where the system is unstable and values where the system stability is assured (periodic motion). This local analysis of the system reduced to the center manifold assures the stable / unstable behavior of the original system around a known solution.
Keywords: Center manifold; equilibrium solution; Non-ideal dynamical systems